2007
DOI: 10.1001/archinte.167.1.31
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Weight Loss on C-Reactive Protein

Abstract: Background: Several studies suggest that weight loss reduces C-reactive protein (CRP) level; however, the consistency and magnitude of this effect has not been well characterized. Our objective was to test the hypothesis that weight loss is directly related to a decline in CRP level. Data Sources:We searched the Cochrane Controlled Trials Register and MEDLINE databases and conducted hand searches and reviews of bibliographies to identify relevant weight loss intervention studies. Study Selection:We included al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
170
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(203 citation statements)
references
References 75 publications
19
170
1
3
Order By: Relevance
“…Since subclinical inflammation increases the risk of cardiovascular disease, disability, neurodegenerative disorders and cancers [20][21][22][23][24], it is important to identify efficient ways to modulate low-grade immune activation. Lifestylebased interventions are one option as they have been proved to exert anti-inflammatory effects in many studies [17,32]. The decrease in CRP and IL-6 levels in response to lifestyle intervention in the Finnish DPS reported here is Data are for intervention and control groups combined, n=406 Correlations are given as (partial) Spearman correlation coefficients, r E%, proportion of total energy derived from the nutrient in question similar to the effects observed in other studies.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Since subclinical inflammation increases the risk of cardiovascular disease, disability, neurodegenerative disorders and cancers [20][21][22][23][24], it is important to identify efficient ways to modulate low-grade immune activation. Lifestylebased interventions are one option as they have been proved to exert anti-inflammatory effects in many studies [17,32]. The decrease in CRP and IL-6 levels in response to lifestyle intervention in the Finnish DPS reported here is Data are for intervention and control groups combined, n=406 Correlations are given as (partial) Spearman correlation coefficients, r E%, proportion of total energy derived from the nutrient in question similar to the effects observed in other studies.…”
Section: Discussionsupporting
confidence: 57%
“…In the Diabetes Prevention Program (DPP), lifestyle intervention achieved median reductions in CRP levels of 33% and 29% between baseline and 1 year in men and women, respectively [16], compared with a median relative reduction in CRP of 27% in the intervention group of the Finnish DPS. When estimating CRP changes per unit of weight loss, a systematic review based on 33 studies showed that, for each kg of weight loss, mean CRP levels declined by 0.13 mg/l [17], whereas a longitudinal study from the UK reported a linear association between CRP levels and weight gain over 9 years (CRP +0.09 mg l −1 kg −1 ) [33]. We report mean CRP reductions and weight loss of 1.24 mg/l and 4.63 kg, respectively, in the intervention group, which resulted in a CRP change of −0.27 mg l −1 [kg weight loss] −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle contraction produces myokines that have anti-inflammatory effects antagonizing the pro-inflammatory cytokines, thus favoring a reduction in inflammation and CRP (Pedersen and Febbraio 2008). Moreover, changes in some body composition components, such as body fat and skeletal muscle mass may play an important role for the reductions in inflammatory levels (Buresh and Berg 2014;Calle and Fernandez 2010;Donges et al 2010;Lee et al 2015;Mavros et al 2014;Selvin et al 2007), and RT has a positive impact on both of these outcomes. On the other hand, some investigations observed that the decrease in CRP is independent of body composition changes (Lera Orsatti et al 2014;Phillips et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is convincing evidence that obesity creates an inflammatory state (44) and that weight loss decreases circulating CRP levels in adults (45,46), controversy surrounds the role of exercise that may occur independently of weight loss; it is postulated that the relative contributions from "fitness" versus "fatness" on inflammatory markers may depend on gender, age, and disease status (47). In this group of disease-free postmenopausal women, the effect of our intervention on CRP levels seemed to have been The TER was calculated from a general linear model for each biomarker, estimating a parameter with anti-logarithm corresponding to the ratio of adjusted geometric means for the exercise intervention group over the control group; this ratio was assumed to be common at 6 months and 12 months postrandomization.…”
Section: Discussionmentioning
confidence: 99%